Enseñanza basada en competencias en el área de Lengua y Literatura en los estudiantes de tercer año de Bachillerato General Unificado del colegio de Bachillerato “27 de Febrero” - Valle Vargas, Lourdes Karina (2023)
The purpose of this research is to analyze the theoretical concepts of Pedagogy based on abilities with the application inside the classrooms in the area of Language and Literature in the level of senior year, of the "27 de Febrero" High School of the city of Loja-Ecuador. The research was qualitative and two Language and Literature teachers were involved. To collect the data, nonparticipant classroom observation and structured interview were the instruments. The outcomes show that the teaching based on abilities in the two teachers is in process of development, due to the evidence in the anticipation, the development, and the consolidation. The applied strategies were: the brainstorming, the essay, and the group work; developed with the intention of promoting an active participation that encourage the pupils. Teachers hardly provide spaces for students to develop autonomous learning and achieve meaningful learning. The teachers' perceptions about the learning based on abilities express that the student must be at the center of the teaching process and the teachers are mediators of teaching and learning. It is concluded that abilities are conceived as skills, attitudes and values that are reflected in the capacity of individuals and, in order for them to be developed in an integral manner, training and updating processes are required for teachers to achieve learning in students.